Revalidating the Positive Achievement Change Tool (PACT) in a Major City: a Survival Analysis - Mueller, Kyle (Crime & delinquency, 2023)
The Positive Achievement Change Tool (PACT) is a popular risk-assessment tool used in juvenile justice systems across the country. This study is an effort at revalidating the PACT in the context of a large Southern city by utilizing days to recidivism in the context of survival analysis. The current research is concerned with whether the PACT?s risk classifications are effective in predicting recidivism. Findings indicate that the PACT effectively predicts recidivism better than chance and that recidivism is especially common early on in probation, with most incidents taking place within the first 200 days. However, the predictive validity of the PACT is not strong for the study population, and its implementation may benefit from context-specific reforms.